Antioxidants in stapedotomy - Fridberger, Anders (Linköping University, 2014)
Background: Otosclerosis is a disorder that impairs middle ear function, leading to conductive hearing loss. Surgical treatment results in large improvement of hearing at low sound frequencies, but high-frequency hearing often suffers. A likely reason for this is that inner ear sensory cells are damaged by surgical trauma and loud sounds generated during the operation. Animal studies have shown that antioxidants such as N-Acetylcysteine can protect the inner ear from noise, surgical trauma, and some ototoxic substances, but it is not known if this works in humans. This trial was performed to determine whether antioxidants improve surgical results at high frequencies.

Methods: We performed a randomized, double-blind and placebo-controlled parallel group clinical trial at three Swedish university clinics. Using block-stratified randomization, 156 adult patients undergoing stapedotomy were assigned to intravenous N-Acetylcysteine (150 mg/kg body weight) or matching placebo (1:1 ratio), starting one hour before surgery. The primary outcome was the hearing threshold at 6 and 8 kHz; secondary outcomes included the severity of tinnitus and vertigo.

Findings: One year after surgery, high-frequency hearing had improved 2.7 ± 3.8 dB in the placebo group (67 patients analysed) and 2.4 ± 3.7 dB in the treated group (72 patients; means ± 95% confidence interval, p=0.54; linear mixed model). Surgery improved tinnitus, but there was no significant intergroup difference. Post-operative balance disturbance was common but improved during the first year, without significant difference between groups. Four patients receiving N-Acetylcysteine experienced mild side effects such as nausea and vomiting.

Conclusions: N-Acetylcysteine has no effect on hearing thresholds, tinnitus, or balance disturbance after stapedotomy

Purpose:

Otosclerosis is a disease of the middle ear that causes gradually increasing hearing loss. The stapes is gradually fixed inside the oval window, which leads to hearing impairment. The conventional treatment is surgical (stapedotomy): The stapes is partially replaced by drilling on its footplate and connecting a prosthesis. This results in great improvement of low-frequency hearing, but at frequencies above 4000 Hz, there is less improvement and in some cases even decline of hearing after surgery (see e.g. Meyer, 1999). This is considered a consequence of trauma to the high-frequency parts of the inner ear during drilling on the stapes footplate. During drilling, patients report loud sounds, often described as ”the worst sound I ever heard”.

In animals, antioxidants such as N-Acetylcysteine can protect the inner ear against noise-induced hearing loss. We will examine whether antioxidants lead to improved high-frequency hearing after stapedotomy. Our hypothesis is that antioxidants protect the inner ear against the trauma caused by the operation.

The dataset contains 9 variables:
"id" is a number with range 1 - 145, unique for each patient.
"medicin" denotes the type of treatment given (possible values are "N-Acetylcysteine" or "Placebo").
"beta" denotes whether the steroid betametason was given before surgery.
"gender" is "f" for female patients and "m" for males.
"weight" is each patient's weight in kg.
"age" is the age (in years, at the time of surgery).
"freq" denotes the type of measurement performed. There are several possible values. "Tinnitus" means that "air1" and "air2" contains the difference in tinnitus scores before and after surgery. "tmv" denotes that air1 contains the average hearing threshold across the frequencies 0.5 - 3 kHz.
"disk" means that "air1" contains the difference in discrimination scores before and after surgery
"dizziness" means that "air1" contains the difference in dizziness scores before and after surgery.
"hearq" means that "air1" contains the difference in hearing quality scores before and after surgery
"surgery" means that "air1" contains the patient's assessment of the outcome of the operation (10 is the best, 0 is the worst)
Numbers "250", "500", "1000", "2000", "3000","4000", "6000" and "8000" means that "air1" contains the difference in hearing thresholds before and after surgery at this particular stimulus frequency.
"air1" contains measurements acquired 6 - 8 weeks after surgery.
"air2" contains measurements acquired 1 year after surgery.

Bakgrund: Otoskleros är en sjukdom som försämrar mellanörats funktion, vilket leder till hörselnedsättning. Kirurgisk behandling förbättrar hörseln vid låga stimuleringsfrekvenser, men högfrekvenshörseln förbättras inte. En trolig anledning till de sämre resultaten vid höga frekvenser är att innerörats sinnesceller skadas av det kirurgiska traumat och ljud som alstras under operationen. Djurstudier har visat att antioxidanter, tex N-Acetylcystein, kan skydda innerörat mot bullerskador, kirurgiskt trauma, och vissa ototoxiska substanser, men det är inte känt om detta fungerar hos människa. Syftet med denna studie är att undersöka om antioxidanter förbättrar kirurgiska resultat vid höga frekvenser.
Metoder: Vi har genomfört en randomiserad, dubbelblind och placebokontrollerad klinisk studie vid tre svenska universitetskliniker. Stratifierad randomisering användes för att slumpa 156 patienter till behandling med antingen intravenöst N-Acetylcystein (150 mg/kg kroppsvikt) eller matchande placebo (kvot 1:1), med start en timme innan operationen. Primärt utfallsmått var hörtröskeln vid 6 och 8 kHz, sekundära effektmått tinnitus och yrsel.
Resultat: Ett år efter operationen hade högfrekvenshörseln förbättrats med 2.7 ± 3.8 dB i placebogruppen (67 patienter analyserade) och med 2.4 ± 3.7 dB i den behandlade gruppen (72 patienter; medelvärde ± 95% konfidensintervall, p=0.54, linjär mixad modell). Operationen förbättrade patienternas tinnitus, men utan signifikant skillnad mellan grupperna. Balansstörningar var vanligt förekommande, men förbättrades under det första året, utan att någon signifikant skillnad mellan grupperna förelåg. Milda biverkningar observerades hos fyra patienter i N-Acetylcysteingruppen (illamående och kräkningar).
Slutsats: N-Acetylcystein påverkar inte hörtrösklar, tinnitus eller balansstörningar efter stapedotomi.

Syfte:

Otoskleros är en öronsjukdom som ger en långsamt tilltagande hörselnedsättning. Stigbygeln fixeras gradvis i ovala fönstret och dess rörelser hämmas, vilket leder till hörselnedsättning. Den gängse behandlingen är kirurgisk (stapedotomi): stigbygelns platta borras upp och man kopplar in en protes som delvis ersätter stigbygeln. Detta ger en stor förbättring av hörseln framförallt vid låga frekvenser, men vid frekvenser ovanför 4000 Hz ses en mindre förbättring och i en del fall tom en försämring efter operationen (se tex Meyer, 1999). Detta anses bero på det trauma som innerörats högfrekvensdelar utsätts för då stigbygelns platta borras upp. Under borrningen upplever patienten starka ljud, som ofta beskrivs som "det värsta jag någonsin hört".

Hos försöksdjur kan antioxidanter, tex acetylcystein, skydda innerörat mot bullerskador. Vi vill undersöka om tillförsel av antioxidanter kan ge förbättrad högfrekvenshörsel efter stapedotomi. Vår hypotes är att antioxidanterna skyddar innerörat mot det trauma som operationen innebär.

The dataset contains 9 variables:
"id" is a number with range 1 - 145, unique for each patient.
"medicin" denotes the type of treatment given (possible values are "N-Acetylcysteine" or "Placebo").
"beta" denotes whether the steroid betametason was given before surgery.
"gender" is "f" for female patients and "m" for males.
"weight" is each patient's weight in kg.
"age" is the age (in years, at the time of surgery).
"freq" denotes the type of measurement performed. There are several possible values. "Tinnitus" means that "air1" and "air2" contains the difference in tinnitus scores before and after surgery. "tmv" denotes that air1 contains the average hearing threshold across the frequencies 0.5 - 3 kHz. "disk" means that "air1" contains the difference in discrimination scores before and after surgery. "dizziness" means that "air1" contains the difference in dizziness scores before and after surgery. "hearq" means that "air1" contains the difference in hearing quality scores before and after surgery. "surgery" means that "air1" contains the patient's assessment of the outcome of the operation (10 is the best, 0 is the worst). Numbers "250", "500", "1000", "2000", "3000","4000", "6000" and "8000" means that "air1" contains the difference in hearing thresholds before and after surgery at this particular stimulus frequency.
"air1" contains measurements acquired 6 - 8 weeks after surgery.
"air2" contains measurements acquired 1 year after surgery.
Antioxidanter vid stapedotomi
Keywords: Hearing; Hörsel; Hearing Loss; Hörselnedsättning; Ear Diseases; Öronsjukdomar; Antioxidants; Antioxidanter; Otosclerosis; Otoskleros; stapedotomy; stapedotomi; prevention; prevention; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Neurosciences; Neurovetenskaper